Hiperplasia adrenal congênita: Quando o sexo precisa ser diagnosticado. Um estudo qualitativo com médicos, pacientes e familiares - Silveira, Mariana Telles [UNIFESP] (2009)
The current scenario regarding treatment of patients with Anomalies of Sex Differentiation (ASD) brings the challenge to put face-to-face the medical knowledge and their patients and/or relatives acquaintance — distinct speeches — so that both these knowledges need to be heard. The general purpose of this work was to identify the anguishes, doubts, distress, and anxieties from patients and their parents, as well as from the medical team that attend them. The specific aim was to evaluate the scenario beyond the medical service in order to appreciate what patients and parents understand or do not understand within the medical attendance and vice-versa. Therefore, interviews were conducted to hear seven specialist physicians from five institutions among the “Sistema Único de Saúde” (SUS), nine parents and six patients bearing the 21-hydroxylase deficiency form of congenital adrenal hyperplasia (CAH).